Religious oblation as a re-proposed model of sequela Christi. Draft of a legal document - MICHOWICZ , PRZEMYSŁAW (Prawo Kanoniczne, 2019)
The main aim of the present paper was to propose, in term of a doctrinal debate, an academic discussion concerning the institution of the oblates as a particular canonical condition of a faithful in the light of legal tradition and current legislation. It was highlighted that oblation is a free act of self-offering to God, recognized by the Church (cf. can. 303 and 677, §2 CIC/1983) whereby individual Christians established a bond intimate union with a particular religious community. The act of oblation is a true offering and brings about a true belonging, though it is different in nature from the bond which unites a religious or a monk to his community and does it not bring about a change in the individual’s status in the Church. In order to embrace every single aspect of the topic, it was necessary to present historical evolution of this ancient institution which, after the promulgation of the first Code of Canon Law in 1917, was not cancelled from the daily praxis of religious institutes. In term of the present reflexions, it was said that oblates are accepted as members of a singular religious community even though their bond is only an obedience bond assumed not as a vow. It was highly recommended that those oblates should have a proper directory containing all rules and regulations pertaining their specific function in the local religious community.